2017
DOI: 10.4209/aaqr.2016.09.0414
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Variations in Particulate Matter in Seoul Associated with Asian Dust and Smog Episodes

Abstract: Particulate species were measured in April-May 2003 at two sites, one in the megacity of Seoul and the other in the Deokjeok Island to the west of Seoul, to examine the effects of long-range transport under the influence of prevailing westerlies. The effects of Asian dust were observed in April, and a severe smog episode occurred in late May. During May, all air pollutants showed negative correlations with wind speed at Seoul, particularly for NO 2 and CO, a large proportion of which result from vehicle emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Accordingly, PCDD/Fs might have travelled from somewhere in northern China to the coastal regions of northern and southern China to Taiwan, suggesting that these pollutants resulted in transboundary pollution because of air-mass transport (Chen et al, 2015;Yang et al, 2017), causing an increase of PCDD/F concentration on the island. A similar phenomenon was also observed before in Korea (Lee et al, 2007;Ghim et al, 2017). PCDD/Fs might also have been brought by air currents from the Pacific Ocean, which are active in the east of Taiwan.…”
Section: Air Mass Trajectories Of Pcdd/fs In Northern Taiwanmentioning
confidence: 60%
“…Accordingly, PCDD/Fs might have travelled from somewhere in northern China to the coastal regions of northern and southern China to Taiwan, suggesting that these pollutants resulted in transboundary pollution because of air-mass transport (Chen et al, 2015;Yang et al, 2017), causing an increase of PCDD/F concentration on the island. A similar phenomenon was also observed before in Korea (Lee et al, 2007;Ghim et al, 2017). PCDD/Fs might also have been brought by air currents from the Pacific Ocean, which are active in the east of Taiwan.…”
Section: Air Mass Trajectories Of Pcdd/fs In Northern Taiwanmentioning
confidence: 60%
“…In Northeast Asia, in particular, precursor emissions and meteorological conditions change markedly depending on the season. Thus, the concentration and composition of PM 2.5 show clear seasonal variations [11,12]. in individual PM 2.5 major chemical components and quantifies foreign impacts, using air-quality modeling; and, finally, Section 4 summarizes our findings.…”
Section: Introductionmentioning
confidence: 90%
“…The zero-out contribution (ZOC) [65] represents the change in concentration when the emission reduction rate of the target area is assumed to be 100%, using the derived sensitivity factor. ZOC was Atmosphere 2020, 11,48 6 of 19 used as the concentration impact of the target emissions in this study. The impact of Chinese emissions on the PM 2.5 concentration in SMA was calculated by adding the ZOCs of each component, in the following manner:…”
Section: Estimation Of Chinese Emission Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, seven day air mass backward trajectories at a height of 3000 m above the ground level were studied using the HYSPLIT model. This model describes the information on the latitude, longitude and altitude of air mass pathways and is useful to identify the probable source regions (Lelieveld et al 2002;Oanh et al 2016;Ghim et al 2017). Schauer et al (2016) have reported the impact of long-range transport of Saharan dust along with emissions from wildfires over a high-altitude site in Austrian Alps.…”
Section: Air Mass Back Trajectory Analysismentioning
confidence: 99%